A novel diterpene agent isolated from Microbispora hainanensis strain CSR-4 and its in vitro and in silico inhibition effects on acetylcholine esterase enzyme - Thawai, Chitti; Bunbamrung, Nantiya; Pittayakhajonwut, Pattama; Chongruchiroj, Sumet; Pratuangdejkul, Jaturong; He, Ya Wen; Tadtong, Sarin; Sareedenchai, Vipaporn; Prombutara, Pinidphon; Qian, Yang (My University, 2020)
An actinomycete strain CSR-4 was isolated from the rhizosphere soil of Zingiber montanum. Taxonomic characterization revealed strain CSR-4 was a member of the genus Microbispora. Whole-genome sequence analysis exhibited the highest average nucleotide identity (ANI) value (95.34%) and digital DNA–DNA hybridization (DDH) value (74.7%) between strain CSR-4 and the closest relative M. hainanensis DSM 45428T, which was in line with the assignment to same species. In addition, a new diterpene compound, 2α-hydroxy-8(14), 15-pimaradien-17, 18-dioic acid, and nine known compounds were isolated from the ethyl acetate crude extract of fermentation broth. Interestingly, a new diterpene displayed the suppressive effect on the recombinant human acetylcholinesterase (rhAChE) enzymes (IC50 96.87 ± 2.31 μg/ml). In silico studies based on molecular docking and molecular dynamics (MD) simulations were performed to predict a binding mode of the new compound into the binding pocket of the rhAChE enzyme and revealed that some amino acids in the peripheral anions site (PAS), anionic subsite, oxyanion site and catalytic active site (CAS) of the rhAChE have interacted with the compound. Therefore, our new compound could be proposed as a potential active human AChE inhibitor. Moreover, the new compound can protect significantly the neuron cells (% neuron viability = 88.56 ± 5.19%) from oxidative stress induced by serum deprivation method at 1 ng/ml without both neurotoxicities on murine P19-derived neuron cells and cytotoxicity against Vero cells.